Cинтез гвинтових конвеєрів-змішувачів з обертовим кожухом - Коваль, С. О.; Koval, S. (ЦНТУ, 2023)
Проведено структурно-схемний синтез гвинтових конвеєрів-змішувачів з обертовим кожухом і згенеровано конструктивні рішення гвинтових робочих органів змішувачів, у яких є можливість вибору необхідної величини зазору між лопатями для інтенсифікації процесу змішування матеріалів різних фракцій, а також конвеєрів-змішувачів з обертовим кожухом без примусового обертання кожуха з можливістю пригальмовування і з примусовим обертанням кожуха з можливістю зміни довжини траси змішування і переміщення матеріалів. Представлено розроблену залежність з допомогою якою проводиться кінцевий відбір синтезованих конструкцій, яка враховує вагу таких факторів, як загальна вартість, продуктивність, ефективність виконання процесу змішування та кількість функціональних характеристик. Carrying out a structural-schematic synthesis often allows you to obtain a significant range of quite effective constructive solutions of various technical means, which fully also applies to the generation of alternative solutions for screw mixers. Screw conveyors-mixers with a rotating casing (GKZOK) are atypical mechanical means for performing the operation of mixing materials, however, they can become quite widely used in various sectors of the economy by combining the operation of moving loose material with the operation of mixing it. For their creation and further research, it is necessary to develop separate rational structures that would meet the relevant parameters in terms of achieving quality indicators of the mixing process, high performance of the process, as well as acceptable cost of manufacturing, operation and maintenance of such structures. For this reason, it is advisable to use the method of structural-schematic synthesis by the method of hierarchical groups with the help of morphological analysis to obtain appropriate technical solutions.
Synthesis of Screw Conveyors-mixers With a Rotating Casing
Keywords: структурно-схемний синтез; гвинтовий конвеєр-змішувач; обертовий кожух; змішування; морфологічний аналіз; гвинтовий робочий орган; structural-schematic synthesis; rotary casing; mixing; morphological analysis; screw working body